Highly efficient dye-sensitized solar cells based on metal-free and copper(II) phthalocyanine bearing 2-phenylphenoxy moiety - ALTUN, SELÇUK; ODABAŞ, ZAFER (ELSEVIER SCI LTD, 2016)
Novel metal-free and copper (II) phthalocyanines containing tetra-(2-phenyl)phenoxy groups were synthesized and characterized. The applicability of these newly synthesised compounds in dyesensitized solar cells (DSSCs) as photosensitizers was studied. The effect of sintering temperature of thick TiO2 film, the sintering temperature was varied from 100 to 500 degrees C, on solar cells parameters has also been investigated. The measurements of the effect of sintering temperature on their performance indicated that the annealing process gives rise to a significant increase in the short current density and the photoconversion efficiency. Interesting results were obtained in TiO2 based solar cell sensitized by 1(4),8(11),15(18),22(25)-tetra-([2-phenyl]phenoxy)phthalocyaninatocopper under optimized conditions. The DSSC devices containing this compound exhibited short-circuit current densities of 12.2 mA cm(-2) and solar energy-to-electricity conversion efficiencies Of 6.81% under AM 1.5 illumination and 100 mW cm(-2) irradiation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Synthesis; Phthalocyanine; 2-Phenylphenol; Dye-sensitized; Solar cells; Photovoltaic; MOLECULAR DESIGN; TIO2 FILMS; PORPHYRINS; ADSORPTION; SURFACE; DONOR